(untitled) (Journal of Food and Dietetics Research, 2022)
Drying is one of the oldest preservation processes available to the mankind, on that we can track since prehistoric times. In today food market dried foods play an important role in the food supply chain. As for fruits and vegetables it can be estimated that they constitute about 1% of the total drying in the food industry Almost 40–50% amount of food items annually are rotten all over the global due to deficiency of proper preservation methods.To extend the shelf life and add value to fresh vegetables, new products may be developed through a drying process. There is a wide range of dried vegetable products such as dried whole vegetable. The objective of the present investigation was to evaluate the effect of pretreatments on the quality characteristics of dehydrated ivy gourd slices and its storage stability. Ivy gourd contains beta-carotene, a major vitamin A precursor from plant sources (Sachan and Chundawat ). It is also a good source of protein, calcium, and fiber. The quality of dried food products may also be improved by the use of various pretreatment methods. The tender green fruits are nutritious and are good source of protein, calcium, fibre and ßcarotene (vitamin A as precursor). Consuming 100 grams of ivy gourd supplies, 1.4 mg of Iron 1.6g of total dietary fiber, 40 mg of calcium and 30 mg of phosphrous (Behl et al., 1993) [4] . In addition to nutrient composition, it is valued for its major biochemical constituents such as alkaloids, glycosides, flavonoids, tannins, saponins have been identified.